2001
DOI: 10.1073/pnas.211431098
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal representations of stimulus associations develop in the temporal lobe during learning

Abstract: Visual stimuli that are frequently seen together become associated in long-term memory, such that the sight of one stimulus readily brings to mind the thought or image of the other. It has been hypothesized that acquisition of such long-term associative memories proceeds via the strengthening of connections between neurons representing the associated stimuli, such that a neuron initially responding only to one stimulus of an associated pair eventually comes to respond to both. Consistent with this hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 40 publications
9
139
0
Order By: Relevance
“…Repeatedly viewing a pair of images close together in time is known to lead to pair coding in the ITC, as manifested in a tendency for neurons to respond with the same strength to both members of the pair (11,12,(15)(16)(17). It merits tangential note that we did observe pair coding, although pair coding was not the main focus of the study.…”
Section: Resultsmentioning
confidence: 55%
“…Repeatedly viewing a pair of images close together in time is known to lead to pair coding in the ITC, as manifested in a tendency for neurons to respond with the same strength to both members of the pair (11,12,(15)(16)(17). It merits tangential note that we did observe pair coding, although pair coding was not the main focus of the study.…”
Section: Resultsmentioning
confidence: 55%
“…9). There is considerable evidence for just this phenomenon in the primate (Higuchi & Miyashita, 1996;Messinger et al, 2001;Miyashita, 1988;Naya et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…A subsequent combined lesion and electrophysiology study further showed that the response of the IT neurons was dependent on the MTL, suggesting the interaction between the MTL and the IT neurons during formation of memory representation (Higuchi and Miyashita, 1996;Messinger et al, 2001). Whereas the role of the hippocampus in long-term memory formation in humans have also been investigated using noninvasive neuroimaging techniques (Stark and Squire, 2000;Haist et al, 2001;Takashima et al, 2006;Smith and Squire, 2009), the neocortical stores for more enduring memory representation largely remain to be explored.…”
Section: Introductionmentioning
confidence: 99%